2005
DOI: 10.1071/ah050017
|View full text |Cite
|
Sign up to set email alerts
|

Performance monitoring in the Victorian health care system: an exploratory study

Abstract: This paper reports on an exploratory study which aims to improve our understanding of how the Chief Executive Officers of Victorian health services monitor strategic and operational performance in their organisations. As a component of a large scale human resource management study, we surveyed 130 Chief Executive Officers (CEOs) of Victorian health sector agencies. Our findings suggest that performance monitoring was more advanced among the larger Victorian health sector organisations, and that there were area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…However, due to the lack of experience in design, implementation and evaluation of the initiatives, the agreements were not clear in purpose and in the targets to be achieved. These problems have been identified in other studies by Leggat et al 31 and Potthoff. 32 Thirdly, inadequate evaluation of the reform initiatives, the lack of opportunity to provide Workforce Planning and Development feedback and the poorly planned implementation process further limited the realisation of the potential.…”
Section: Discussionsupporting
confidence: 66%
“…However, due to the lack of experience in design, implementation and evaluation of the initiatives, the agreements were not clear in purpose and in the targets to be achieved. These problems have been identified in other studies by Leggat et al 31 and Potthoff. 32 Thirdly, inadequate evaluation of the reform initiatives, the lack of opportunity to provide Workforce Planning and Development feedback and the poorly planned implementation process further limited the realisation of the potential.…”
Section: Discussionsupporting
confidence: 66%
“…The metropolitan hospital CEOs reported linking the financial results to the greatest extent (88 per cent), with some linking of the service indicators but less emphasis on linking clinical indicators. In contrast, the regional (71 per cent) and district (100 per cent) hospitals and community health centres (71 per cent) reported the greatest focus on linking patient satisfaction measures, compared with only 38 per cent of the metropolitan hospital CEOs (Leggat et al. , 2005).…”
Section: Procedures and Resultsmentioning
confidence: 97%
“…Finally, the study also demonstrated limited performance monitoring throughout the Victorian public health sector. The sector reported a strong focus on financial, activity and patient satisfaction measures, with limited reporting on HR measures (Leggat et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance goals need to be Specific, Measurable, Attainable but challenging, Relevant and recorded, and have a Timeframe for achievement (Mealiea & Latham 1996: 35), and be Trackable or easily monitored. Although many public sector organisations monitor organisational performance, few have been able to effectively link the performance indicators to the managers' and staff performance goals (Griffiths 2003;Leggat, Bartram & Stanton 2005). A key requirement for managers is to relate the individual performance goals of their staff to the broader organisational goals.…”
Section: Goal Settingmentioning
confidence: 99%